STUDI PENGARUH PASANG SURUT AIR LAUT TERHADAP KAPASITAS OUTFALL SALURAN DRAINASE KOTA MAKASSAR - Andi Muh. Subhan Saiby; Hasdaryatmin Djufri, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The problem of flooding in Makassar City often occurs every year during the rainy season, where when floods occur, inundation ranges from 0.5 m to 1.5 m, almost completely inundating residential areas. The aim of this research is to analyze the capacity of one of the outfall drainage channels in Makassar City based on conditions when the highest tides occur and rain occurs with a return period of 25 years. Modeling was carried out using the EPA SWMM program on the outfall between Dermaga Polair and the Swiss Bell Hotel. Modeling scenario with tidal input with the highest rang of tide for 24 hours and rainfall intensity with a return period of 25 years. The subcatchment area includes the area bounded by Jalan Sudirman-Jalan Ahmad Yani-Jalan Kartini at the channel upstream. The modeling results show that the channel outfall is still greater than the water passing through due to the influence of rain and tides. The highest water level occurs at 06:00 AM and the lowest water level occurs at 09:00 PM